2016
DOI: 10.1111/exd.13106
|View full text |Cite
|
Sign up to set email alerts
|

Monopathogenic vs multipathogenic explanations of pemphigus pathophysiology

Abstract: This viewpoint highlights major, partly controversial concepts about the pathogenesis of pemphigus. The monopathogenic theory explains intra-epidermal blistering through the "desmoglein (Dsg) compensation" hypothesis, according to which an antibodydependent disabling of Dsg 1-and/or Dsg 3-mediated cell-cell attachments of keratinocytes (KCs) is sufficient to disrupt epidermal integrity and cause blistering. The multipathogenic theory explains intra-epidermal blistering through the "multiple hit" hypothesis sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 128 publications
(150 reference statements)
0
83
0
7
Order By: Relevance
“…Rather, Ca 2+ and Erk signaling may be additionally required for epidermal blistering. However, since pemphigus pathogenesis is complex and autoantibodies against other antigens can be present as well 10, 42, 46, 47 , we do not expect that the signaling patterns are similar in each patient. For cAMP signaling, which was proposed to be a salvage pathway in PV by limiting p38MAPK activation and Dsg3 depletion 28 , we observed that levels of cAMP were elevated in response to m-PV-IgG and mc-PV-IgG only but not to AK23, at-PV-IgG or PF-IgG.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rather, Ca 2+ and Erk signaling may be additionally required for epidermal blistering. However, since pemphigus pathogenesis is complex and autoantibodies against other antigens can be present as well 10, 42, 46, 47 , we do not expect that the signaling patterns are similar in each patient. For cAMP signaling, which was proposed to be a salvage pathway in PV by limiting p38MAPK activation and Dsg3 depletion 28 , we observed that levels of cAMP were elevated in response to m-PV-IgG and mc-PV-IgG only but not to AK23, at-PV-IgG or PF-IgG.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, Ca 2+ and Erk signaling pathways were restricted to IgG fractions containing aDsg1 only. Importantly, we cannot definitely conclude whether autoantibodies directed against Dsg1 were primarily responsible for signaling because additional antibodies present in the polyclonal IgG fractions may also be involved 42 . The identification of signaling pathways activated by specific desmosomal and non-desmosomal autoantibodies should be a primary focus for future studies.…”
Section: Discussionmentioning
confidence: 96%
“…However, in very rare cases of pemphigus vulgaris, IgG autoantibodies against desmocollin 3 (another desmosomal cadherin) can cause the disease phenotype without coexisting anti-desmoglein autoantibodies 41,42 . In addition to desmoglein and desmocollin, other autoimmune targets have also been found with various approaches 31,4345 . Although their potential role in the pathogenesis of pemphigus is still under investigation, these non-desmoglein autoantibodies might have some supporting roles and contribute the complex phenotype of pemphigus or might have pathogenic roles on their own that are sufficient for blister formation in rare cases.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…PV is caused by autoantibodies to desmogleins 3 and 1 and clinically manifests as blisters and erosions on the skin and/or close‐to‐surface mucous membranes, whereas PF results from autoantibodies to desmoglein 1, and its blistering phenotype is typically restricted to the skin . Autoantibodies blocking the function of other target antigens, including cholinergic receptors of the keratinocyte membrane involved in intercellular adhesion, have also been described in pemphigus …”
Section: Introductionmentioning
confidence: 99%